Reconstructing The Boundary Between Juvenile Delinquency and Crime as a Foundation for Juvenile Justice System Reform - Lidya Dayana Sakti Negara; Fauzie Yusuf Hasibuan; Maryano Maryano (Sahabat Publikasi, 2026)
The purpose of this research is to critically analyze the issue of unclear boundaries between the two concepts and to formulate a normative foundation that can serve as the basis for reconstructing a more proportionate and just juvenile criminal justice system. Employing a normative legal research approach with prescriptive analysis, the study reviews statutory regulations, doctrines of juvenile criminal law, and systematically selected academic literature. The findings reveal that the conflation of developmental misconduct with criminal behavior contributes to excessive criminalization of children, weakens the rehabilitative orientation of juvenile justice, and generates legal uncertainty in law-enforcement practices. The discussion situates these findings within theories of child development, the principle of the best interests of the child, and modern criminal-law paradigms that position punishment as an ultimum remedium. The article argues that juvenile justice reform cannot rely solely on procedural mechanisms such as diversion and restorative justice, but must begin with a conceptual reconstruction of the boundaries of juvenile criminal responsibility. The study’s contribution lies in strengthening a normative framework that distinguishes juvenile delinquency from criminal conduct in order to promote a more proportional, humane, and child-centered juvenile justice system. This framework is expected to inform policymakers, law-enforcement authorities, and scholars in developing consistent and rights-based juvenile justice policies aligned with international child-protection standards and restorative justice principles within democratic rule-of-law systems that respond to contemporary social change and long-term child-development challenges both globally and nationally.